Las regiones de montañas como espacios de oportunidad para la integración bioceánica: el ejemplo del paso de Jama en los Andes Centrales - Kanitscheider, Sigrun; Bender, Oliver (Revista de Geografía Norte Grande, 2021)
In policy debates, improving the transport infrastructure in the Andes is seen as a key factor for the economic development of peripheral regions. Taking the case of the newly widened trunk road through the Central Andes between Argentina and Chile, based on official statistics I will identify the traffic flows actually generated by the mountain pass road at regional and global scale. However, the development potential of an international transport link through the high mountain area cannot be assessed on the economic justification of the road alone. Many other factors come into play here. They stem from the natural landscape, from political, legal as well as ethnic-historical contexts. I shall explore these factors in the case study and present their persistence vis-a-vis changes. This opens up the possibility of analysing the economic significance of an existing mountain pass road for the development of the region as well as gauging such significance for proposed road construction projects